Identità, differenza e conflitto nel pensiero di Martin Heidegger, Carl Schmitt e Massimo Cacciari - Sferrazza Papa, Ernesto (Filosofia, 2018)
This article aims at interpreting the logical and metaphysical categories of identity and otherness as political constructs. I will start with a discussion of Fichte’s identity principle, then I will proceed to explore Massimo Cacciari’s interpretation, by showing the inherently discursive character of the aforementioned principle. I will then analyze the political meaning of the conceptual couple identity-otherness through the reflections of Martin Heidegger and Carl Schmitt. The political ontology proposed by these authors serves as a theoretical framework for the revision of some fundamental categories of the contemporary politico-philosophical debate. Within this conceptual framework, which must be embedded in the global space we live in, the concepts of ‘enemy’ and ‘conflict’ take on a major role, both from a political and strategic viewpoint.